Guide to building control for domestic buildings - Gwynne, Anthony (Wiley-Blackwell, 2013)
"This guide provides clear explanations of how the technical design and construction requirements of the Building Regulations can be met. It gives sufficient information to draw up an effective specification and design to be developed. It covers commercial and domestic building, restoration and conservation work: commercial guidance including industrial, residential, healthcare and education buildings; and domestic guidance for extensions, loft conversions, new dwellings, conversions (garages and barns), listed buildings. The guide presents information contained in the building regulations and approved documents in an easy-to-understand format, clear, concise and fully illustrated. Typical section details have been provided for all the more common construction methods used"--